2017
DOI: 10.1097/tp.0000000000001469
|View full text |Cite
|
Sign up to set email alerts
|

Intragraft and Systemic Immune Parameters Discriminating Between Rejection and Long-Term Graft Function in a Preclinical Model of Intestinal Transplantation

Abstract: We studied acute and chronic rejections in a preclinical model of ITX, which recapitulates clinical findings and highlights the importance of monitoring peripheral T cell activation inhibitor-mitochondrial expression, LBP levels, and antidonor antibodies for revealing rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…However, only a few studies have reported the association between LBP and rejection after solid organ transplantation. Gerlach et al showed that plasma LBP levels increased during acute and chronic rejections after intestinal transplantation in rats [ 36 ], and Freue et al reported that seven plasma proteins including LBP were increased in recipients with biopsy-proven acute rejection [ 37 ]. A case–control discovery study by the Genome Canada Biomarkers in Transplantation Group showed that LBP was one of the proteomic signatures in the plasma during early acute kidney allograft rejection.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few studies have reported the association between LBP and rejection after solid organ transplantation. Gerlach et al showed that plasma LBP levels increased during acute and chronic rejections after intestinal transplantation in rats [ 36 ], and Freue et al reported that seven plasma proteins including LBP were increased in recipients with biopsy-proven acute rejection [ 37 ]. A case–control discovery study by the Genome Canada Biomarkers in Transplantation Group showed that LBP was one of the proteomic signatures in the plasma during early acute kidney allograft rejection.…”
Section: Discussionmentioning
confidence: 99%
“…Allograft rejection after kidney transplantation is the main factor affecting the long-term survival of renal allograft ( Gerlach et al, 2017 ; Wang et al, 2017 ; Nunes-Dos-Santos et al, 2020 ). According to its mechanism, rejection episodes following renal transplant can be classified into T-cell-mediated rejection (TCMR) and humoral rejection ( Rodríguez-Perálvarez et al, 2017 ; Haas, 2018 ).…”
Section: Introductionmentioning
confidence: 99%